Las múltiples acepciones del término “historia” durante la Primera República en Nueva Granada, 1809-1815 (2016)
ABSTRACT: This study explores the assorted connotations that the elite Creole press ascribed to the term “history” during Nueva Granada’s First Republic between 1809 and 1815. This investigation brings to light evidence of two diverse uses of the concept history. One depicts the magistra vitae perspective and the other one portrays a more modern notion regarding the passage of time. Articles written by Antonio Nariño in La Bagatela are clear examples of the latter case.